2015
DOI: 10.1103/physrevb.91.075305
|View full text |Cite
|
Sign up to set email alerts
|

Optical control of spin textures in quasi-one-dimensional polariton condensates

Abstract: We investigate spin transport through polarization-resolved spectroscopy by propagating polariton condensates in a quasi-one-dimensional microcavity ridge along macroscopic distances. Under circularly polarized, continuous-wave, nonresonant excitation, a sinusoidal precession of the spin in real space is observed whose phase depends on the emission energy. The experiments are compared with simulations of the spinor-polariton condensate dynamics based on a generalized Gross-Pitaevskii equation, modified to acco… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 56 publications
3
22
0
Order By: Relevance
“…However, in more recent experiments, a higher total degree of polarization was reported under circularly polarised non-resonant pulsed excitation rather than for linearly polarised excitation [27]. Moreover in polariton spin textures generated under circularly polarised excitation a high DCP was reported in the vicinity of the pump spot [16,17]. These experiments confirmed that there are correlations between the polarisation of the optical excitation with the polarisation of the condensate, which in GaAs/AlGaAs MCs are not screened from optical disorder.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, in more recent experiments, a higher total degree of polarization was reported under circularly polarised non-resonant pulsed excitation rather than for linearly polarised excitation [27]. Moreover in polariton spin textures generated under circularly polarised excitation a high DCP was reported in the vicinity of the pump spot [16,17]. These experiments confirmed that there are correlations between the polarisation of the optical excitation with the polarisation of the condensate, which in GaAs/AlGaAs MCs are not screened from optical disorder.…”
Section: Introductionsupporting
confidence: 72%
“…Initial realizations of resonant polariton spinswitches [15], followed by experimental demonstrations of extensive polariton spin transport in planar [16] as well as 1D structures [17], has emphasized the potential of theoretical propositions for fully integrated polariton based spin circuits [18,19]. The short lifetime of polaritons considered to be an impediment for thermodynamic equilibrium and bosonic condensation can now be seen as an advantage in creating ultra-fast spin switching devices.…”
Section: Introductionmentioning
confidence: 99%
“…Such a reservoir can be controllably replenished by a pump laser of the selected polarization, thus opening up the way to create and manipulate spinor condensates of excitonpolaritons in the regime of incoherent far off-resonant optical excitation 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The angle of detection ( ) is directly related to the parallel component of the polariton momentum, k//, by k// . Low temperature (10 K) continuous wave photoluminescence (PL) measurements (not shown) reveal that the emission spectrum of the sample is composed of a broad band between 1.5480 eV and 1.5420 eV, originating from the excitonic recombination [35] together with several narrow lower polariton branches (LPBs), between 1.5420 eV and 1.5398 eV, arising from the confinement along the narrow dimension of the ridge. Under resonant excitation conditions the phase of the polariton condensates would be inherited from that of the laser pulses, therefore to study the genuine condensates' coherence we excite quasi-resonantly, at 1.5459 eV.…”
Section: Resultsmentioning
confidence: 99%